Global trends in research related to functional dyspepsia and anxiety or depression over the past two decades: a bibliometric analysis - Huang, Qian; Yuan, Huixiao; Li, Qingqing; Li, Yang; Geng, Shasha; Zhu, Yingqian; Liao, Min; Jiang, Hua (Frontiers in Neuroscience, 2023)
Background and purpose: Functional dyspepsia (FD) is a prevalent global disorder of the upper digestive tract characterised by functional impairment. It often coexists with anxiety/depression, significantly impairing occupational productivity and overall quality of life. This study aimed to identify emerging patterns and prominent themes within FD and anxiety/depression research through bibliometric analysis to help explore new innovative avenues for investigating this type of FD. Methods: A comprehensive review of literature encompassing FD and anxiety/depression was conducted using the Science Citation Index Extension of the Web of Science Core Collection from 2003 to 2023. Information extracted comprised “Full Record and Cited References”. Bibliometric analysis of relevant publications, including country, institution, author, journal, citations, and keywords, was conducted using CiteSpace, VOSviewer, and Bibliometrix package in R and Excel. Results: Studies related to FD and anxiety/depression have demonstrated an ascending trajectory since 2003. Our bibliometric analysis identified 338 studies published by 2023. NEUROGASTROENTEROLOGY AND MOTILITY emerged as the most prolific journal, while GASTROENTEROLOGY retained pre-eminence within the top 10 published journals. China emerged as the most prolific country, with two institutions within the top 10 in terms of volume of publications. The Mayo Clinic stood as the foremost institution in terms of publication volume, with the Chengdu University of Traditional Chinese Medicine exhibiting robust collaborative engagement. Eminent author influence was attributed to Talley NJ of Newcastle University, Australia. Clusters of extensively cited papers and prevalent keywords delineate the status and trend of FD and anxiety/depression research. This encompasses FD, anxiety, depression, sleep disorders, and functional gastrointestinal disorders. Furthermore, the timeline view map or trend-term analysis suggested that duodenal low-grade inflammation ("duodenal eosinophilia" and "mast cells") might be a new concern associated with FD and anxiety/depression. Conclusions: Employing bibliometric analysis, this study revealed prevalent focal areas and new trends within FD and anxiety/depression research. These insights serve as valuable guidance for scholars seeking to delve into new research avenues.